Sharpening the coach`s eye: An observational study investigating the trainability of an eye-tracking strategy for perceiving barbell velocity loss in resistance training - Ben-Ari, A.; Henry, S.; Halperin, I.; Carey, L.; Iacono, A. D. (Sports Medicine - Open, 2026)
Background :Resistance training (RT) coaches can implement velocity-based training (VBT) to prescribe set volume by terminating sets at a target velocity loss (VL) threshold. However, VBT necessitates velocity-tracking devices that demand time and expertise. In a previous study, we asked RT coaches to detect VL thresholds using solely their observational judgment - the Coach`s Eye. We found improved accuracy when participants spontaneously used a "bar strategy" (focusing on the barbell). Here, we investigated whether coaches could be trained to intentionally use this strategy and whether it would be associated with greater accuracy in detecting VL thresholds. Methods: Twenty RT coaches completed one experimental session involving a gaze strategy training intervention. Participants watched an instructional video on the bar strategy, practiced with gaze feedback, and completed a VL detection task. The task involved watching videos of trainees performing bench presses and back squats and detecting 20% and 40% VL thresholds. We examined the frequency of bar strategy use using a one-sided exact binomial test and the accuracy in VL thresholds detection using a negative binomial mixed-effects model. Results: Participants used the bar strategy in most trials (mean proportion = 78.81, 95% CI [0.75, 1.00]). The average absolute error in detecting VL thresholds was 1.5 (SD = 2.3) repetitions. Error decreased when using the bar strategy (-1.23, 95% CI [-1.99, -0.03]), detecting 40% VL thresholds (-1.60, 95% CI [-1.88, -1.26]) compared to 20%, and observing sets loaded with 85% 1RM (-1.59, 95% CI [-1.93, -1.16]) but not with 65% 1RM (-0.48, 95% CI [-1.01, 0.18]) compared to 45% 1RM. Lastly, mental fatigue did not significantly affect accuracy (-0.01, 95% CI [-0.03, 0.01]). Conclusions: This study provides novel evidence that, under laboratory conditions, RT coaches can be trained to use a gaze strategy associated with improved accuracy in detecting barbell VL. Thus, the Coach`s Eye may offer a practical, coach-led complement to velocity-tracking devices in VBT, with further studies in real-world settings required to establish its ecological validity.